123 EVALUATION OF REMNANT CHOLESTEROL LEVELS AND MONOCYTE -TO-HDL -CHOLESTEROL RATIO IN PATIENTS WITH MYOCARDIAL INFARCTION WITH NORMAL CORONARY ARTERIES. (15th December 2022) - Di Fazio, Luca; Coppola, Giuseppe; Novo, Giuseppina; Galassi, Alfredo R; Corrado, Egle; Sucato, Vincenzo
Abstract: Background: Myocardial Infarction with Non-Obstructive Coronary Arteries (MINOCA) is a pathology characterized by clinical evidence of myocardial infarction (according to the 4 th Universal Definition of Myocardial Infarction) with normal or near-normal coronary arteries. This condition is extremely variable in etiology, pathogenic mechanisms, clinical manifestations, prognosis and therapeutic approach. Several studies have been described new markers as independent predictors of acute coronary events, severe coronary disease and major adverse cardiovascular events (MACEs), like remnants of cholesterol and monocyte/HDL-C ratio. These new markers have never been studied in MINOCA. The objective of the study is the evaluation of remnant cholesterol (RC) and monocyte/HDL-C ratio (MHR) in patients with MINOCA, in order to establish their validity as predictors of this event. Materials and Methods: We enrolled 114 patients who received diagnosis of MINOCA and performed a coronary angiography compared to 110 patients without previous cardiovascular events. Data were analyzed consulting medical records and related attachments. Remnants were calculated with the following formula: RC = Total Cholesterol (TC) – HDL-C – LDL-C. Since laboratory findings were obtained from blood samples at admission, we determined non-fasting remnants. The difference between levels of fasting and post-prandial circulating RC is irrelevant, so we could perform an accurate estimation of RC levels. Monocyte/HDL-C ratio was calculated by dividing monocytes count of peripheral blood by HDL-C levels; platelet/lymphocyte ratio was obtained by dividing platelet count by lymphocyte count. We have also calculated various lipoproteins ratios, like TC/HDL-C, LDL-C/HDL-C, Triglicerides/HDL-C, non-HDL-C/HDL-C. Results: Patients with MINOCA had higher mean levels of RC (21, 3 ± 10, 6 vs 13, 2 ± 7, 7 mg/dL), monocyte/HDL-C ratio (23±0, 009 vs 18, 5± 8, 3) and platelet/lymphocyte ratio (179, 8 ± 246, 1 vs 135 ± 64, 7) rather than the control group. Only the mean values of all calculated lipoproteins ratios were lower in MINOCA patients. Statistical significance was achieved only in the remnant cholesterol evaluation. Conclusions: Higher levels of RC and monocyte/HDL-C ratio were found in patients with MINOCA, compared to patients without previous cardiovascular events. We also observed higher levels of platelet/lymphocyte ratio rather than the control group. Only various lipoprotein ratios resulted lower in MINOCA group. This finding could reflect the extreme heterogeneity underlying the pathogenetic mechanism of MINOCA. Unlike patients with MI-CAD, therefore, dyslipidemia could play a minor role in the pathogenic mechanism of MINOCA. In patients who receive diagnosis of MINOCA with a baseline alteration of the lipid profile and higher levels of cholesterol at admission as well, the evaluation of these parameters could play an important role, providing more detailed informations about their cardio-metabolic risk. Nevertheless, further studies with larger samples are needed to validate these parameters in clinical practice.